212k views
1 vote
Factor completely 3x2+7x-6​

2 Answers

3 votes

Answer:

Explanation:

(3x - 2)(x + 3)

User Odysseas
by
5.1k points
2 votes

3x2 + 7x - 6

Multiply the 3 and -6 together to get -18 .

What two numbers add to 7 and multiply to -18 ? → +9 and -2

So...we can split the middle term like this...

= 3x2 + 9x - 2x - 6 Now factor a 3x out of the first two terms.

= 3x(x + 3) - 2x - 6 Now factor a -2 out of the last two terms.

= 3x(x + 3) - 2(x + 3) Now factor a (x + 3) out of both remaining terms.

= (x + 3)(3x - 2)

User Joshuahealy
by
5.8k points